1996
DOI: 10.1183/09031936.96.09071470
|View full text |Cite
|
Sign up to set email alerts
|

Combined smoke inhalation and body surface burns injury does not necessarily imply long-term respiratory health consequences

Abstract: This study was undertaken to assess the long-term respiratory health consequences of smoke inhalation in patients who are burns survivors.Patients with smoke inhalation resulting from domestic flame or fire were studied. Medical records were the primary source for the selection of the patients. Smoke inhalation was diagnosed on the basis of the visual appearance of the airways on the reported bronchoscopy. Patients who participated in the study were compared on important characteristics with those who did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Mlcak et al 6 ) reported that burn injury patients with inhalation injuries displayed a ventilatory rather than a cardiac limitation to exercise. Furthermore, Bourbeau et al 7 ) found that long-term pulmonary function was impaired but not below normal limits, and that exercise tolerance was unchanged in adults following inhalation injury. Conversely, Willis et al 8 ) demonstrated that adults with burn injuries, with and without inhalation injury, had a significantly lower aerobic capacity and greater oxygen desaturation during a maximal oxygen exercise test compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Mlcak et al 6 ) reported that burn injury patients with inhalation injuries displayed a ventilatory rather than a cardiac limitation to exercise. Furthermore, Bourbeau et al 7 ) found that long-term pulmonary function was impaired but not below normal limits, and that exercise tolerance was unchanged in adults following inhalation injury. Conversely, Willis et al 8 ) demonstrated that adults with burn injuries, with and without inhalation injury, had a significantly lower aerobic capacity and greater oxygen desaturation during a maximal oxygen exercise test compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Uzun dönem; çoğu hasta, duman inhalasyonundan sonra uzun süreli fonksiyonel bozulma yaşamaz. Şiddetli duman inhalasyonu öyküsü olan 23 hastanın incelendiği bir çalışmada, spirometri, nonspesifik hava yolu aşırı duyarlılığı veya kardiyak parametreler maruziyetten yaklaşık dört yıl sonra ölçüldüğünde hiçbir değişiklik olmamıştır (55) . Ancak bir derlemede solunum fonksiyon bozukluğu yapan toksik inhalasyonu da olan ciddi yanıklı çocuklarda, akciğer fonksiyonunun yaralanma sonrası 10 yıla kadar düşük saptandığı belirtilmiştir (38) .…”
Section: Prognozunclassified
“…Conversely, Bourbeau et. al described that exposure to smoke inhalation from a fire does not necessarily result in long-term respiratory effects up to 45 months post-injury [5,19]. Further, one study did not find inhalation injury had any effect on quality of life, though was limited to the pediatric population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining long-term outcomes of inhalation injury are limited by small sample sizes or animal models [3][4][5][6]. Default proxy for diagnosis of inhalation injury is through history and physical exam, as only a few diagnostic procedures have been proposed and validated [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%